If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -4x + -2(3) = 2 + 5x + 1(2) Multiply -2 * 3 8 + -4x + -6 = 2 + 5x + 1(2) Reorder the terms: 8 + -6 + -4x = 2 + 5x + 1(2) Combine like terms: 8 + -6 = 2 2 + -4x = 2 + 5x + 1(2) Multiply 1 * 2 2 + -4x = 2 + 5x + 2 Reorder the terms: 2 + -4x = 2 + 2 + 5x Combine like terms: 2 + 2 = 4 2 + -4x = 4 + 5x Solving 2 + -4x = 4 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 2 + -4x + -5x = 4 + 5x + -5x Combine like terms: -4x + -5x = -9x 2 + -9x = 4 + 5x + -5x Combine like terms: 5x + -5x = 0 2 + -9x = 4 + 0 2 + -9x = 4 Add '-2' to each side of the equation. 2 + -2 + -9x = 4 + -2 Combine like terms: 2 + -2 = 0 0 + -9x = 4 + -2 -9x = 4 + -2 Combine like terms: 4 + -2 = 2 -9x = 2 Divide each side by '-9'. x = -0.2222222222 Simplifying x = -0.2222222222
| 6a^2=-15a | | 8-4x-2=2+5x+1 | | 2(6x-5)+8=3(2x-5)+1 | | 142=(3x+6)+(9x-8) | | 5(2x-5)=3(x+4) | | 6(x-5)=3(x+12) | | -5(x-7)=-90 | | 5N*-1= | | 4x-8+x=3(2x-5)-6 | | 9(5+t)-2(t+1)= | | 7x+14=3x-30 | | -4+3r-7(2s-r)83= | | 8(5-2x)+4=3-2(x+6) | | -7+7x=6x+14 | | 5x-6+2x+12=90 | | -7(1+x)=-6x-13 | | (2x+7)(3x^2-16x+16)=0 | | 5f+j=8mn | | G+51=42 | | 3(4x+9)=5-2(5+2x) | | 8b+3-10=-2+3 | | 2x+6=10x-18 | | 2y-6y+2=31 | | 5(2-3n)=2-15n | | -40-8k=2(-7k-8) | | 8q-3+5q(2+q)= | | N+25=61 | | 6x+2(2-2x)=2x+4 | | 4gm-8h=7j | | 4x-15=2x+7 | | 3v+9=5 | | 5f+j=8m |